Trade, development and financial services issues in CARICOM - Chaitoo, Ramesh ([Caribbean Regional Negotiating Machinery] [Christ Church]BB, 2006)
Addresses CARICOM-wide issues regarding the regional financial services sector. Presents an overview of OECS and CARICOM trade. Argues that there is an urgent need in the OECS and CARICOM to shift their trade from goods to services exports, and to diversify their services export profile.